Rationale, Ideas, and Approaches for the Revision of the Writing Section in the Unified Junior High School Chinese Textbooks - RONG Weidong; ZHU Yuguo (Jiaoshi jiaoyu xuebao)
The revision of the writing section in the unified junior high school Chinese textbook aligns with the ideas, goals, and requirements of the new Chinese curriculum standard. It follows the principle of "adhering to tradition while innovating, and seeking progress while maintaining stability."Adjustments have been made to various aspects such as writing perspectives, writing types, topic setting, and writing guidance, retaining the strengths and characteristics of the original textbooks meanwhile. Specific revisions include adding five writing themes, merging some repeated content, removing outdated themes, improving writing topics, and further refining the writing guidance system. The new textbook particularly emphasizes new forms of writing, such as situational task writing, critical thinking writing, and creative writing, aiming to comprehensively enhance students' new writing skills. To adapt to the new textbook, it is recommended to recognize the importance of writing instruction and establish a specialized awareness; adhere to a competency-oriented approach and foster new writing concepts and teaching perspectives; enhance the professionalism of writing instruction with evidence-based practice; adopt corresponding teaching strategies based on different writing types; focus on writing process guidance, writing strategies, and writing scaffold design; and fully utilize the textbook as the primary channel for curriculum resources.